The Relationship between Social Support of Principal and Self-compassion of School Counselors to the Performance of School Counselors - Salsabila, Revitia Thalita; Istaryatiningtias, Istaryatiningtias; Khuluqo, Ihsana El (Universitas Muhammadiyah Metro, 2024)
In this study, 115 participants were randomly chosen using a lottery system. Three research instruments, including a social support instrument with 32 valid items and a reliability coefficient of 0.769, were used to compile the study's findings on a Likert scale. Cronbach's alpha for the 26 self-compassion instrument items is 92. There were 15 legitimate elements included in the performance instrument, and its reliability coefficient was 0.878. Concurrent findings from two tests, with a Fcount of 5.203 (Fcount>Ftable) and a 0.007 significance level. These findings suggest a causal link between school counselors' social support and self-compassion and their effectiveness. The values (r) 0.437 and 0.243 with significance (p 0.007) and (p 0.009) demonstrate a favorable association between social support and performance and self-compassion to the performance, respectively. With an R2 of 0.298, we can say that social support and self-compassion contribute effectively to performance by 29.8 percent. With an adequate contribution of 21.4% for social support and just 8.4% for self-compassion, it is clear that social support has a stronger association with performance. This study found that school counselors in Central Jakarta who reported higher levels of social support and self-compassion also reported better levels of job satisfaction.